Dinamika Hubungan Antara Media Dan Praktisi Public Relations Dalam Konteks Krisis Organisasi - Adinda Risqiana Dewi Maulana (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This research adopts a qualitative approach with a literature review design, exploring the interaction between media and Public Relations (PR) during crisis situations. Utilizing secondary data sources such as journals and books, this study investigates the factors influencing the collaboration between media and PR, as well as effective communication strategies in crisis management. Data analysis identifies common patterns, themes, and trends emerging from the reviewed literature, providing a comprehensive understanding of the dynamics of the relationship between media and PR during crises. The research findings highlight the importance of transparency, prompt responsiveness, and solid collaboration between media and PR in effectively managing crises. The contribution of this study lies in deepening the understanding of the vital role of collaboration between media and PR in safeguarding the reputation and image of companies during crisis situations.